Keanekaragaman Serangga pada Tanaman Cabai Merah Di Desa Kubangwungu Kecamatan Ketanggungan Kabupaten Brebes - Dwi Yuliani; Devi Ayu Susilowati; Anton Maulana Ibrahim (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
The increasing number of population and the growing food industry that requires raw material for red chilies have led to an increase in demand for red chilies. The research was conducted using a survey method which was carried out from February 2021 to April 2021. Sampling of insect diversity was carried out on 1,000 m2 of red chili plantations. The land for the red chili plants was determined by 10 points randomly. Each sampling point consisted of 2 pitfall traps, 1 light trap, and 1 insect net with 4 replications. Insect sampling was carried out when the chili plants began to enter the generative period (44-50 days after planting) for 6 consecutive days, in this phase the insect pests began to be seen in many chili plants. The results of the sampling were then identified using the J. Borror (1992) determination key book. Analysis of insect diversity data was carried out by calculating the diversity index (diversity) based on Magurran (1988) using the Shannon-Evenness Index and the Shannon-Evenness Index. The results showed that 28 species consisted of the order hemiptera, coleopteran, prthoptera, diptera, hymenoptera, odonata, mantodea, and Lepidoptera. The results showed that the diversity index of insect pollinators on red chili agricultural land using the pit fall method (H´ = 2.874) was lower than the light (H '= 3.029) and netting methods (H' = 3.0159), while the evenness index on land The pit fall method of red chili farming (E = 0.8627) was lower than the light method (E = 0.909) and netting method (E = 0.9481). Keywords: diversity, insects, red chilies